Pengaruh Kepemilikan Publik, Kompleksitas Operasi dan Komite Audit Terhadap Audit Delay - Thalia Loviana Cipta; Sophia Andini (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The research aims to determine and analyze the influences of public ownership, complexity of operations and audit committee on audit delay. The population in research are all companies in the mining sector which were listed on the Indonesia Stock Exchange (IDX) in the 2014-2018 period. The sampling technique uses purposive sampling which produces total sample of 26 companies with total research data of 130 observations. The research used multiple regression analysis with random effect approach model. The partial test results show that public ownership has positive influence on audit delay while complexity of operations and audit committee has no influence on audit delay.